PENGARUH MODAL SOSIAL MASYARAKAT PEDESAAN TERHADAP KEBERHASILAN PEMBANGUNAN DESA DI KECAMATAN PINELENG KABUPATEN MINAHASA - Ontorael, Meditran; Sondakh, Telly; Laloma, Alden (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTACK: This research Along with the reform era, the organization of local government to change with the implementation of regional autonomy widely, real, and responsible. Based on the results of the initial observations indicate that tingka outcomes on development in villages in the subdistrict Pineleng not optimal. This condition can be observed from the socio-economic conditions / livelihood of people is still relatively low, where the number of underprivileged families are still quite high, while the Tertiary participation and independence of the community also showed a similar reality.This type of research used is descriptive and explanatory survey by using quantitative and qualitative approach, which aims to obtain an overall picture of the mapping and the benefits of social capital for the success of rural development in the district Pineleng Minahasa district ..Based on the results of the descriptive analysis, it is known that the social capital variables are at low and medium categories are respectively 34.34%, followed by the category of "high" of 31.31%. Meanwhile, variaDbel success of rural development in the category of "low" tend to be moderate, amounting to 44.44% and 43.43%, and only 12.12% are categorized high. Statistical analysis showed that the hypothesis that social capital of rural communities and a significant positive effect on the success of rural development in the District Pineleng Minahasa regency.Keywords: Effects of Social Capital Rural Communities Against Rural Development Success In District Pineleng Minahasa District.